Utilization of Quizizz Digital Media in Arabic Language Learning at SD Muhammadiyah Ambarketawang 3 - Nur Azizah Samsudin; Ari Purnawan (Green Publisher Indonesia, 2025)
Advances in digital technology have transformed Arabic language learning methods. This study aims to analyze the use of digital media, particularly the Quizizz application, in Arabic language learning at SD Muhammadiyah Ambarketawang 3. It employs a descriptive qualitative approach, utilizing non-participatory observation and structured interviews with two Arabic language teachers who have 5–8 years of teaching experience in grades 4–6. Data were analyzed using thematic analysis following Miles and Huberman's framework, including data reduction, data display, and conclusion drawing/verification, with methodological triangulation to ensure validity. The results indicate that using Quizizz, YouTube, and PowerPoint in Arabic language learning boosts student motivation, listening and writing skills, and enables a more flexible evaluation process. Students showed higher engagement levels, with teachers reporting improved istima' (listening) and kitabah (writing) competencies. Quizizz's interactive features, including real-time feedback and gamification elements, emerged as key factors in sustaining student interest. Despite challenges such as technical constraints related to internet connectivity, limited device availability, and teachers' adaptation to new pedagogical approaches, digital media proved effective in enhancing learning quality. This study recommends ongoing teacher training to optimize learning technology use and institutional investment in digital infrastructure to support sustainable technology-enhanced Arabic language instruction.